2020
DOI: 10.7454/ihpa.v5i3.3378
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Preparedness Level and Policy Implementation Analysis of Hospital Disaster Plan in RSUD Kota Yogyakarta

Abstract: Hospital is a public facility that must continue on full operation when a disaster occurs. In any disaster situation that results in a surge in patients, hospitals are expected to provide health services for the victims. This study uses  mixed research methods. We combine qualitative methods using in-depth interviews and quantitative methods using questionnaires and hospital safety index scoring. The sample was taken by purposive sampling on hospitals’ management incorporated in the disaster management organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
2
3
0
1
Order By: Relevance
“…The study's findings revealed that hospitals' preparedness for the management of health emergencies and disasters is low, with an overall preparedness score of 54.75 %. This finding is consistent with a similar study conducted in western Ethiopia, Tunisia, Jeddah, and Italy, but it is lower than that of an Indonesian study [27] , [28] , [29] , [30] , [31] . The variation may be due to geographical differences, which may interfere with institutions' perceptions of disaster risk according to the nature of the disaster in that specific location [32 , 33] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study's findings revealed that hospitals' preparedness for the management of health emergencies and disasters is low, with an overall preparedness score of 54.75 %. This finding is consistent with a similar study conducted in western Ethiopia, Tunisia, Jeddah, and Italy, but it is lower than that of an Indonesian study [27] , [28] , [29] , [30] , [31] . The variation may be due to geographical differences, which may interfere with institutions' perceptions of disaster risk according to the nature of the disaster in that specific location [32 , 33] .…”
Section: Discussionsupporting
confidence: 91%
“…According to the findings in this study, the logistics and finance domains had the lowest level of preparation in this study, which was similar to the findings in western Ethiopia and Indonesia [27 31] . This could be due to the fact that health care services in general, and emergency mass causality management in particular, are resource expensive, posing an additional burden for resource-constrained countries like Ethiopia [44] .…”
Section: Discussionsupporting
confidence: 89%
“…Disaster management relies on a collaborative team approach with clear roles and responsibilities assigned to each staff member involved in MCIs management. 24 Usually during MCIs, hospitals mobilize their entire staff, 25 , 26 an act that fosters a sense of teamwork and collaboration needed for effective MCI management, which is also the case in this study. However, staff inadequacy, excessive workloads, and the lack of knowledge and experience among newly recruited staff on the hospital’s disaster plan and their roles and responsibilities during MCIs are all challenges which small district hospitals frequently encountered.…”
Section: Discussionmentioning
confidence: 81%
“…Persentase Penurunan Kadar Glukosa Darah Mencit (Geniosa & Aini, 2020). Untuk mengetahui seberapa besar kemampuan menurunkan kadar glukosa darah pada hewan coba dari pemberian sediaan uji yang digunakan, maka digunakan rumus persentase penurunan kadar glukosa darah yaitu :…”
Section: Pengujian Aktivitas Antioksidan Dan Anti-hiperglikemik Herba...unclassified